Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am studying Statistical Mechanics and Thermodynamics from a book that i am not sure who has written it, because of its cover is not present.

There is a section that i can not understand:


$S= \sum_{j=1}^{N} F_{j}$

$<S>=< \sum_{j=1}^{N} F_{j}> = \sum_{j=1}^{N} <F_{j}>$

$\sigma^{2}_{S} =<S^{2}>-<S>^{2}$

line a:

$=\sum_{j=1}^{N}\sum_{k=1}^{N} <F_{j}F_{k}> - \sum_{j=1}^{N} <F_{j}>\sum_{k=1}^{N}<F_{k}>$

line b:

$=\sum_{j=1}^{N}\sum_{k=1(k\neq j))}^{N} <F_{j}><F_{k}> +\sum_{j=1}^{N} <F_{j}^{2}> - \sum_{j=1}^{N} <F_ {j}>\sum_{k=1}^{N}<F_{k}>$

line c:

$=\sum_{j=1}^{N} (<F_{j}^{2}>-<F_{j}>^{2})$ $=\sum_{j=1}^{N} \sigma_{j}^{2}$

My question is what happened after line a to line b and after that to line c?

My other question is, i have a little math, what should i study to understand such thermodynamics root math studies, calculus 1 or 2 or what else, can you specify a math topic?


share|cite|improve this question
up vote 1 down vote accepted

I'll use a much simpler notation for starters, going to drop $\langle$ and $\rangle$. So the first term in line a is


and if you write it explicitly you have

$\sum_{i}\sum_{j}A_iA_j=(A_1A_1+A_2A_2+\dots+A_nA_n)+(A_1A_2+A_1A_3+\dots+A_1A_n)+\dots+(A_nA_1+A_nA_2+\dots+A_nA_{n-1})=\sum_iA_{i}^2+A_1\sum_{i\ne1}A_i+A_2\sum_{i\ne2}A_i+\dots+A_n\sum_{i\ne n}A_i=\sum_i A_{i}^2+\sum_i\sum_{j\ne i}A_iA_j$

So this gives you term one and two in line b. The third term in line b stays the same. Now for the last line when you take the following difference

$\sum_{j=1}^{N}\sum_{k=1(k\neq j))}^{N} <F_{j}><F_{k}> - \sum_{j=1}^{N} <F_ {j}>\sum_{k=1}^{N}<F_{k}>$ you get

$\sum_{j=1}^{N} <F_{j}>^2$

this is because the first double sum contains only terms like $F_iF_j$ and the second sum cointains terms like $F_iF_i$ and $F_iF_j$. So when you take the difference all the terms $F_iF_j$ will cancel out and your left with $\langle F_i\rangle\langle F_i\rangle=\langle F_i\rangle^2$. Thus you find your final result.

share|cite|improve this answer
thanks very much. i understood very well – merveotesi Apr 4 '13 at 7:31
Hello, i have a question, what is the difference between $=\sum_{j=1}^{N}\sum_{k=1}^{N} <F_{j}F_{k}>$ and $\sum_{j=1}^{N} <F_ {j}>\sum_{k=1}^{N}<F_{k}>$ ? – merveotesi Jun 14 '13 at 11:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.